Integrated computer package for productivity, cost control and schedule control / Mohd Zukri Jaafar - Jaafar, Mohd Zukri (1993)
Recently , there are so many computer softwares sold in the market and its purpose is to overcome complex tasks which must be carried out continuously. In this final year project paper , the software which is called IHPROMA ( Stands for integrated PROject MAnagement ) is compiled using Quickbasic language . This software does productivity calculations and then prepares a datafile for other control accounts such as job cost control and schedule control system to produce labor ledger, labor distribution, job cost ledger, monthly cost statement and labor cost report. From all those accounts, we can monitor the progress by using schedule control system. This software enables the project manager to monitor productivity on site and it has also the capability to integrate the productivity on site with accounting system for job cost control system and schedule control system.